Maternal Mortality in the United States: We Must Do Better. Issue 1 (January 2017) - Simpson, Kathleen Rice
Abstract : In the United States, maternal death is more common than in many other developed countries and while there have been decreases in maternal mortality in other countries, there have been increases here. The continued rise in maternal deaths is a health crisis and a national tragedy that can be addressed in part with everyone working together to adopt evidence based childbirth practices and by reviewing near miss cases as a team.